Establishment of new drought-tolerant varieties of Cenchrus purpureus - Wright-Ramírez, Jorge Valentín (2026)
Introduction. Drought can reduce grain production by up to 50 % and significantly reduce the biomass of pastures and forages intended for animal feed. Objective. To evaluate the establishment of ten new varieties of Cenchrus purpureus tolerant to drought under conditions of intense seasonal drought in the Cauto Valley, Cuba. Materials and methods. A randomized block design with four replicates was used to evaluate ten new varieties of Cenchrus purpureus (CT-600, CT-601, CT-602, CT-603, CT-604, CT-605, CT-606, CT-607, CT-608 and CT-609) on Fluvisol soil in an area of intense seasonal drought in Cuba, from November 2019 to May 2020. The CT-115 variety was used as a control. During the sprouting phase, soil moisture, plant height, leaf area, biomass yield, and leaf-to-stem ratio were monitored and calculated. Results. During the first 12 days after planting, varieties CT-608, CT-607, CT-609, CT-600, CT-603 and CT-115 showed higher sprouting percentages (p ² 0.05), this trend was maintained until day 19. CT-603 and CT-608 reached the highest sprouting capacity, exceeding 60 % at 29 days, followed by CT-600 and CT-609 with more than 50 %, and then CT-607 with 44 % (p ≤ 0.05). The remaining varieties, including the control, exhibited slower sprouting, with values ranging from 20 to 40 % during that period. Conclusions. At the establishment cut, no significant differences were found between varieties in terms of height, growth, leaf area, and dry matter (DM) yield; however, biomass structure indicators varied, with only CT-604 surpassing the control in leaf-to-stem ratio (2.1 vs. 1.5) and leaf percentage (67.4 vs. 57.8 %). The new varieties demonstrated the capacity to successfully establish under the conditions evaluated.